2021
DOI: 10.1007/s11255-021-02909-4
|View full text |Cite
|
Sign up to set email alerts
|

Testicular shear wave elastography in oligo-astheno-teratozoospermic individuals: a prospective case–control study

Abstract: Purpose The primary objective of this study was to evaluate the testicular stiffness by ultrasound shear wave elastography (SWE) both in men with oligo-astheno-teratozospermia (OAT) and in control group. The secondary objective was to identify a possible correlation between semen quality with testicular stiffness. Methods This was a prospective case-control study. We divided the sample in two groups; Group A (case group) included men with OAT, and Group B … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 21 publications
(27 reference statements)
1
4
0
Order By: Relevance
“…Men with OAT had higher testicular stiffness value than the controls in both sides. These studies consistent with our results (Camoglio et al, 2017; Illiano et al, 2021).…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…Men with OAT had higher testicular stiffness value than the controls in both sides. These studies consistent with our results (Camoglio et al, 2017; Illiano et al, 2021).…”
Section: Discussionsupporting
confidence: 94%
“…Consistent with our results, Illiano et al analysed 100 participants, including 50 patients in case group and 50 controls, they found men with OAT had higher testicular stiffness than the controls in both sides, men with abnormal semen parameters showed an inverse correlation between the mean value of testicular stiffness and TMC, SC and progressive motility, while the correlation was not evident in the control group. Abnormal semen parameters mean that the spermatogenic function of the testicle is damaged, which is also largely affected by the destruction of testicular ultrastructure, including seminiferous tubules and spermatogenic cells (Illiano et al, 2021). Fuschi et al used SWE to assess the correlation between semen parameters of VC patients and testicular histological changes in a prospective study, they found that there was a statistically significant difference in SWE between VC testicles and the contralateral testicles.…”
Section: Discussionmentioning
confidence: 99%
“…In men with oligoasthenoteratozoospermia (OAT), Illiano et al noted a higher mean SWE value in both testicles when compared to men with normal semen parameters (left testicular stiffness 21.4 ± 5.4 kPa vs. 9.9 ± 1.6 kPa, p < 0.0001; right testicular stiffness 22.9 ± 4.8 kPa vs. 9.5 ± 2.4 kPa, p < 0.0001). The same study showed negative correlations between the testicular stiffness and total sperm count, concentration and progressive motility [ 61 ].…”
Section: 2 Testiclementioning
confidence: 96%
“…Other radiological techniques for the diagnosis and staging of PCa are recently emerging, such as multiparametric US (mpUS), whole-body MRI (WB-MRI), and PSMA PET/MRI; however, they are still supported by limited evidence [12]. Several other imaging modalities were proposed to improve the management of patients with urological tumors (e.g., Near-Infrared Fluorescence), but very limited data are currently available in the PCa setting [13][14][15].…”
Section: Introductionmentioning
confidence: 99%